ARTERIAL HYPERTENSION AND ARRHYTHMIA - Khaydarova Zarrina Erkinovna; Khusainova Munira Alisherovna; Makhmudova Khanuza Davranovna (Journals Park Publishing, 2024)
According to the Framingham study, predictors of atrial remodeling may be an increase in the maximum duration and dispersion of the P wave measured on a standard ECG. Material and methods: A prospective case—control study included 41 patients (mean age 58.4 = 8.6 years). Retrospectively, according to the clinical and instrumental examination, stage I-II hypertension and the recurrent form of AF were verified. The control group consisted of 21 patients without hypertension and fp. Depending on the type of myocardial remodeling, 3 comparison groups were formed from patients with hypertension: the 1st group consisted of 18 patients with concentric LV remodeling (CLVR), the 2nd — 13 men and women with concentric LV hypertrophy (CLVH), the 3rd — 10 examined with eccentric LV hypertrophy (ELVH). Results and discussion: At the same time, attacks of AF and ventricular tachycardia persisted, were accompanied by calls from ambulance crews and, in 32.1% of cases, hospitalizations. However, subsequently, the appointment and constant intake of these drugs (the second year) allowed to reduce the number of arrhythmic complications, and after 2 years, patients noted a decrease in arrhythmia attacks, their better tolerability. Conclusions: In patients with arterial hypertension, long-term administration of β-blockers, angiotensin converting enzyme inhibitors, angiotensin receptor blockers and preductal reduces the risk of atrial fibrillation and ventricular arrhythmias.
Keywords: risk of arrhythmic complications, arterial hypertension.